THE EFFECT OF PROFIT SHARING FINANCING, BOPO, NPF AND FDR ON THE PROFITABILITY OF SHARIA PEOPLE'S FINANCING BANKS IN CENTRAL JAVA PROVINCE IN 2021-2023 - Endang Puji Lestari; Mutia Pamikatsih; Hatta Setiabudhi (Universitas Islam Darul 'ulum Lamongan, 2025)
Abstract This research is a quantitative study on Sharia People's Financing Banks in Central Java Province which are registered with the OJK (Financial Services Authority). This study aims to examine the effect of profit sharing financing, BOPO, NPF and FDR on profitability proxied through ROA (Return On Asset). The type of data used is secondary data in the form of quarterly financial reports obtained from the OJK official website. The sampling method used is non probability sampling with purposive sampling technique. The analysis method used is descriptive statistical analysis, determination of the estimation model, panel data linear regression, classical assumption test and hypothesis testing using Eviews 12 software. The results showed that profit sharing financing and NPF partially had a positive and insignificant effect on ROA, BOPO partially had a negative and significant effect on ROA, and FDR partially had a negative but insignificant effect on ROA. Profit sharing financing, BOPO, NPF and FDR simultaneously affect ROA. The four variables have the ability to affect ROA by 35.41%, while the remaining 64.59% is influenced by other variables not included in the research model.